2015
DOI: 10.1158/1541-7786.mcr-15-0204
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol Targets LRP6 to Inhibit Wnt Signaling in Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive malignancy in need of more effective treatment approaches. One potential therapeutic target is Wnt/β-catenin signaling, which plays important roles in PDAC tumor initiation and progression. Among Wnt inhibitors with suitable in vivo biological activity is vitamin D, which is known to antagonize Wnt/β-catenin signaling in colorectal cancer and have anti-tumor activity in PDAC. For this study the relationship between vitamin D signaling, Wnt/β-catenin acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 49 publications
(73 reference statements)
0
27
0
Order By: Relevance
“…1,25D3 exerts its actions via binding with and modulating the vitamin D receptor (VDR), a transcriptional regulator [11][12][13]. 1,25D3 also activates Wnt/β-catenin to facilitate osteoblast differentiation [14][15][16]. Conversely, 1,25D3 induces Dickkopf-1 (DKK1) transcripts to suppress Wnt/β-catenin in bladder and colon cancers [17,18], suggesting that 1,25D3 has tissue-specific effects on Wnt/β-catenin signaling.…”
Section: Introductionmentioning
confidence: 99%
“…1,25D3 exerts its actions via binding with and modulating the vitamin D receptor (VDR), a transcriptional regulator [11][12][13]. 1,25D3 also activates Wnt/β-catenin to facilitate osteoblast differentiation [14][15][16]. Conversely, 1,25D3 induces Dickkopf-1 (DKK1) transcripts to suppress Wnt/β-catenin in bladder and colon cancers [17,18], suggesting that 1,25D3 has tissue-specific effects on Wnt/β-catenin signaling.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Recent studies in laboratory models of pancreatic cancer have demonstrated the therapeutic potential of vitamin D analogs by engagement of VDR in tumor cells and supportive cells within the tumor stroma. [6][7][8] Although studies that have evaluated circulating vitamin D and pancreatic cancer incidence have been conflicting, 9,10 few studies have been conducted to assess the association of vitamin D levels with survival in patients with pancreatic cancer. 11,12 To assess the potential prognostic effect of vitamin D status, we evaluated the association between prediagnostic plasma 25-hydroxyvitamin D [25(OH)D] and overall survival among patients with pancreatic cancer drawn from five large US prospective cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of LRP6 contributes to the hyperactivation of the Wnt/β-catenin signaling pathway, which could promote the progression and invasion of various tumors, including hepatocellular carcinomas, colorectal cancer, prostate cancer, breast cancer, and pancreatic cancer. 59 , 74 , 75 Aberrant function of LRP6 is also related to many other diseases, such as autosomal-dominant oligodontia, Alzheimer’s disease, atherosclerosis, and diabetic retinopathy. In the male reproductive system, Wnt/β-catenin signaling plays important roles in the differentiation of Müllerian duct, organization of testicular cords, development of primordial germ cells, and proliferation and differentiation of spermatogonia.…”
Section: Discussionmentioning
confidence: 99%